2022
DOI: 10.3390/foods11213333
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Drying Technology of Tomato Pulp with Phytoene, Phytofluene and Lycopene Retention as Inspection Indexes

Abstract: The objective was to design a feasible drying method to increase the retention rates of phytoene (PT), phytofluene (PTF) and lycopene (LYC) in tomato powder. The method was to compare the effects of vacuum freeze-drying (FD), vacuum drying (VD) and hot-air drying (HAD) technologies on tomato pulp rich in PT, PTF and LYC. When dried by HAD, the retention rates of PT, PTF and LYC decreased significantly (p < 0.05) only when the water content decreased from 30% to 3.5%. When dried by VD, the temperatures had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Tomatoes are a nutritional food source in many diets all over the world and are known to provide a number of health benefits. This is mostly because they contain carotenoids such as lycopene and β-carotene, which have antioxidant properties and protect against heart disease and other health conditions [1][2][3][4][5][6]. Tomatoes supply more than 85% of the lycopene required for human nutrition since they are widely consumed in both fresh and tomato-related products [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomatoes are a nutritional food source in many diets all over the world and are known to provide a number of health benefits. This is mostly because they contain carotenoids such as lycopene and β-carotene, which have antioxidant properties and protect against heart disease and other health conditions [1][2][3][4][5][6]. Tomatoes supply more than 85% of the lycopene required for human nutrition since they are widely consumed in both fresh and tomato-related products [7].…”
Section: Introductionmentioning
confidence: 99%
“…These reactions are mainly caused by the exposure to light, heat, and oxygen because carotenoids present unsaturated double bonds [9,18]. Moreover, it was observed that dried tomato samples have higher lycopene and β-carotene contents than fresh samples due to the improvement of the extraction process caused by the reduction of the sample moisture [2].…”
Section: Introductionmentioning
confidence: 99%